Effects of dietary cholesterol in diabetes and cardiovascular disease. (December 2014) - Fernandez, Maria Luz; Andersen, Catherine J
Dietary cholesterol has received a lot of attention in regards to its potential association with both heart disease and Type 2 diabetes from health professionals and the general public. There is ample evidence from epidemiological data, meta-analysis reports and clinical interventions on the lack of a relationship between dietary cholesterol and heart disease risk. However, current reports appear to indicate that increased dietary cholesterol may be associated with an increased risk for heart disease in diabetic patients. Further, the relationship between dietary cholesterol and diabetes risk has not reached a consensus in the current literature and clinical studies have failed to prove that increased dietary cholesterol affects glucose metabolism or insulin resistance, indicating the need for more prospective and clinical studies. The current review will address the controversies from studies focusing on the associations and/or lack of correlation between dietary cholesterol and heart disease as well as dietary cholesterol and diabetes.